Pengaruh Pendekatan Matematika Realistik Berbasis Kearifan Lokal terhadap Kemapuan Pemecahan Masalah Matematis Siswa SMP - Setiawan (Medan Resource Center, 2022)
One of the reasons for the low ability to solve mathematical problems is the lack of an active role in understanding and finding and finding the information or data that will be opened. One of the learning strategies used to develop students' problem-solving skills is the PMR approach based on local wisdom. The purpose of this study was to determine the effect of learning with the PMR approach based on local wisdom on mathematical problem solving for junior high school students. This study uses a quantitative approach where the data obtained in the form of tests are tested statistically. The population in this study were all seventh grade students of SMP Negeri 1 Samudera, while the samples were class VII-2 as the experimental class, and class VII-3 as the control class. From the results of statistical data processing, it was found that the average value of the experimental class was significantly different from the control class, so it can be found that the application of a local wisdom-based mathematical approach to the mathematical problem solving abilities of SMP Negeri 1 Samudera students.